Sosialisasi dan Pendampingan Sertifikasi Halal bagi UMKM di Desa Wangkelang, Kecamatan Moga, Kabupaten Pemalang - Sidik Asrofi; Masruroh Masruroh; Tamimatul Isnaini; Evi Yuswiayanti; Hendri Hermawan Adinugraha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas KH. A. Wahab Hasbullah, 2023)
Currently, the issue of halal has become an important economic issue, where halal products are considered as high quality products and therefore have a higher value than other economic sectors. The purpose of this community service activity is to provide socialization and understanding related to the halal label to MSME actors in Wangkelang Village, Moga District, Pemalang Regency. This community service program was carried out in Wangkelang Village, Moga District, Pemalang Regency by visiting MSME actors in the local area. The process of activities carried out in this community service starts from the initial preparation stage, implementation of training, and reporting of the results of community service in the community service journal regarding the socialization and assistance of halal certification to MSMEs. The results of the service show that there is a real increase in understanding after MSME actors are given training and assistance regarding halal product certification.